Analysis of The Implementation of Nosocomial Infection Prevention and Control in Hospitals (A Literature Study) - Amira Mhuthia Adila; Nur Ramadhan; Puspa Nujulla; Putri Dwi Ardiyanti; Rina Oktavia; Shelly Fadhilah Muqsith; Vania Alda Nabilah; Zalma Nur Khadijah Putri; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Infections due to health services or Healthcare-Associated Infection (HAI) or known as nosocomial infections are infections that occur in patients during treatment in hospitals or other health facilities. The prevention and control of nosocomial infections is a worldwide challenge. This study aims to examine the literature, articles, or journals of research results regarding the implementation of prevention and control of nosocomial infections in hospitals. The method used is a literature review with 10 journals that were reviewed and written from 2015 to 2020, or written in the last 6 years with the keywords